2003
DOI: 10.1094/mpmi.2003.16.11.1003
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol Traits of Pseudomonas spp. Are Regulated by Phase Variation

Abstract: Of 214 Pseudomonas strains isolated from maize rhizosphere, 46 turned out to be antagonistic, of which 43 displayed clear colony phase variation. The latter strains formed both opaque and translucent colonies, designated as phase I and phase II, respectively. It appeared that important biocontrol traits, such as motility and the production of antifungal metabolites, proteases, lipases, chitinases, and biosurfactants, are correlated with phase I morphology and are absent in bacteria with phase II morphology. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 59 publications
2
62
1
Order By: Relevance
“…P. fluorescens CHA0 (wild type), CHA19 (⌬gacS), CHA89 (gacA::Km), CHA810 (⌬rsmZ), CHA822 (⌬rsmY), CHA825 (⌬rsmY ⌬rsmZ), CHA1003 (rsmE::⍀-Hg), CHA1008 (⌬gacS rsmE::⍀-Hg rsmA::⍀-Km), CH A1009 (rsmE::⍀-Hg rsmA::⍀-Km), and CH A1076 (rsmA::⍀-Km) and their derivatives carrying chromosomal hcnAЈ-ЈlacZ or aprAЈ-ЈlacZ fusions have been described (14,15,18,19,24). Strains carrying a chromosomal rsmEЈ-ЈlacZ fusion were constructed by using pME7545 for delivery (29). Growth conditions, antibiotic concentrations, and conditions for ␤-galactosidase assays were the same as those previously used (14,15,18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…P. fluorescens CHA0 (wild type), CHA19 (⌬gacS), CHA89 (gacA::Km), CHA810 (⌬rsmZ), CHA822 (⌬rsmY), CHA825 (⌬rsmY ⌬rsmZ), CHA1003 (rsmE::⍀-Hg), CHA1008 (⌬gacS rsmE::⍀-Hg rsmA::⍀-Km), CH A1009 (rsmE::⍀-Hg rsmA::⍀-Km), and CH A1076 (rsmA::⍀-Km) and their derivatives carrying chromosomal hcnAЈ-ЈlacZ or aprAЈ-ЈlacZ fusions have been described (14,15,18,19,24). Strains carrying a chromosomal rsmEЈ-ЈlacZ fusion were constructed by using pME7545 for delivery (29). Growth conditions, antibiotic concentrations, and conditions for ␤-galactosidase assays were the same as those previously used (14,15,18).…”
Section: Methodsmentioning
confidence: 99%
“…Whereas in plant-and animalpathogenic species GacS͞GacA is important for virulence (20,(25)(26)(27), the same system is required for biocontrol in plantbeneficial strains (19,20,24,28,29). We have previously reported that, in P. fluorescens CHA0, GacS͞GacA positively controls transcription initiation of two small RNA genes, rsmZ and rsmY (14,18).…”
mentioning
confidence: 99%
“…Most phase-and antigenic-variable proteins have important roles in mediating interactions between bacteria and their environments (393,395). They control the formation of the capsule (428), the pili (429), flagella (430), adhesins (431), antifungal metabolites (432), iron acquisition factors (433), and other surface-exposed molecules (432,434), sometimes affecting motility (432) or colony morphology (434) and opacity (374). Nevertheless, these proteins can also be involved in general cellular pathways, such as DNA restrictionmodification (435), gene regulation (436), or metabolism (437).…”
Section: Consequences Of Genome Instability In Bacteria Phase and Antmentioning
confidence: 99%
“…Given the broad influence of the GacS-GacA system on bacterial physiology, it is striking that spontaneous gacS and gacA mutants (i.e., Gac Ϫ mutants) emerge and accumulate in cultures of Pseudomonas spp. (17,(21)(22)(23)(24)(25)(26)(27). Colonies of these mutants can be distinguished from those of the wild type visually by their expanded colony size, flattened appearance, increased fluorescence under UV light, and lack of extracellular protease production (21,24).…”
mentioning
confidence: 99%